2017
DOI: 10.1007/s11336-017-9565-x
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Ideal Point Classification Models for Bivariate Binary Data

Abstract: The ideal point classification (IPC) model was originally proposed for analysing multinomial data in the presence of predictors. In this paper, we studied properties of the IPC model for analysing bivariate binary data with a specific focus on three quantities: (1) the marginal probabilities; (2) the association structure between the two binary responses; and (3) the joint probabilities. We found that the IPC model with a specific class point configuration represents either the marginal probabilities or the as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…De Rooij (2009) also showed that a simple logistic regression for binary response variable can be written as a unidimensional IPC model. Worku and De Rooij (2016) extended the IPC model to the analysis of two binary response variables, i.e., the bivariate, binary data setting, and showed that a new parameterization of the IPC model recovered both the marginal probabilities and the association structure of bivariate binary data well. However, this parameterization cannot be easily extended to handling multivariate binary data because all the possible pairwise and higher order association terms must be specified in the likelihood function, which makes the model complex and therefore hard to estimate.…”
Section: Introductionmentioning
confidence: 99%
“…De Rooij (2009) also showed that a simple logistic regression for binary response variable can be written as a unidimensional IPC model. Worku and De Rooij (2016) extended the IPC model to the analysis of two binary response variables, i.e., the bivariate, binary data setting, and showed that a new parameterization of the IPC model recovered both the marginal probabilities and the association structure of bivariate binary data well. However, this parameterization cannot be easily extended to handling multivariate binary data because all the possible pairwise and higher order association terms must be specified in the likelihood function, which makes the model complex and therefore hard to estimate.…”
Section: Introductionmentioning
confidence: 99%